Analysis of the negative-bias-temperature-instability on omega-gate silicon nanowire soi mosfets with different dimensions - Silva, Vanessa C. P.; Wirth, Gilson I.; Martino, João A.; Agopian, Paula G. D. [UNESP] (Journal of Integrated Circuits and Systems, 2020)
This work presents an experimental analysis of the Negative-Bias-Temperature-Instability (NBTI) on omegagate nanowire (NW) pMOSFETS transistors and the trends analysis from simulations, focusing on the influence of channel length and width, since it is an important reliability parameter for advanced technology nodes. 3D-numerical simulations were performed as guideline for a trend analysis. The results show a high NBTI in NW (ΔVT≈200-300mV – for WNW=10nm) due to a high defect density and high gate oxide electric field accelerating the NBTI effect providing a higher degradation.
Keywords: MOSFET; NBTI; NW; SOI